Suprathel®‐assisted surgical treatment of the hand in a dystrophic epidermolysis bullosa patient. Issue 5 (11th February 2014) - Sari, Elif; Eryilmaz, Tolga; Tetik, Gulsum; Ozakpinar, Hulda R; Eker, Esabil
Abstract Epidermolysis bullosa (EB) is a progressive familial disorder composed of dermal mucosal blisters, flexion contractures and pseudosyndactylies. Flexion contractures and pseudosyndactyly can be treated with surgery but usually require skin grafting. Because of poor wound healing, skin graft harvesting is a challenge in these patients. In order to prevent donor‐site morbidities due to skin graft harvesting some alloplastic materials were introduced. In this study, we focused on Suprathel® as a new allograft material for covering the skin defects of a patient with dystrophic EB.